High-throughput sequencing of retrotransposon integration provides a saturated profile of target activity in Schizosaccharomyces pombe - Guo, Yabin; Levin, Henry L.

(untitled) (Genome Research, 2010)
The biological impact of transposons on the physiology of the host depends greatly on the frequency and position of integration. Previous studies of Tf1, a long terminal repeat retrotransposon in Schizosaccharomyces pombe, showed that integration occurs at the promoters of RNA polymerase II (Pol II) transcribed genes. To determine whether specific promoters are preferred targets of integration, we sequenced large numbers of insertions using high-throughput pyrosequencing. In four independent experiments we identified a total of 73,125 independent integration events. These data provided strong support for the conclusion that Pol II promoters are the targets of Tf1 integration. The size and number of the integration experiments resulted in reproducible measures of integration for each intergenic region and ORF in the S. pombe genome. The reproducibility of the integration activity from experiment to experiment demonstrates that we have saturated the full set of insertion sites that are actively targeted by Tf1. We found Tf1 integration was highly biased in favor of a specific set of Pol II promoters. The overwhelming majority (76%) of the insertions were distributed in intergenic sequences that contained 31% of the promoters of S. pombe. Interestingly, there was no correlation between the amount of integration at these promoters and their level of transcription. Instead, we found Tf1 had a strong preference for promoters that are induced by conditions of stress. This targeting of stress response genes coupled with the ability of Tf1 to regulate the expression of adjacent genes suggests Tf1 may improve the survival of S. pombe when cells are exposed to environmental stress.